The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1515/zpch-2018-1168
|View full text |Cite
|
Sign up to set email alerts
|

Transient Spectroscopy of Glass-Embedded Perovskite Quantum Dots: Novel Structures in an Old Wrapping

Abstract: Semiconductor doped glasses had been used by the research and engineering communities as color filters or saturable absorbers well before it was realized that their optical properties were defined by tiny specs of semiconductor matter known presently as quantum dots (QDs). Nowadays, the preferred type of QD samples are colloidal particles typically fabricated via organometallic chemical routines that allow for exquisite control of QD morphology, composition and surface properties. However, there is still a num… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…At higher pump intensities, multiple excitons can be generated. By subtracting the relaxation process of single exciton using the previously reported method, , the biexciton lifetimes of CsPbI 3 NCs in different specimens are fitted (Figure S6). The results show that the biexciton lifetime increases from 9.9 ± 0.5 ps (HT47012, Figure S6a) to 25.1 ± 0.8 ps (HT48010, Figure S6b), 19.8 ± 0.4 ps (HT48012, Figure S6c), 51.2 ± 3.7 ps (HT49010, Figure S6d), and 83.9 ± 4.4 ps (HT50010, Figure S6e).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At higher pump intensities, multiple excitons can be generated. By subtracting the relaxation process of single exciton using the previously reported method, , the biexciton lifetimes of CsPbI 3 NCs in different specimens are fitted (Figure S6). The results show that the biexciton lifetime increases from 9.9 ± 0.5 ps (HT47012, Figure S6a) to 25.1 ± 0.8 ps (HT48010, Figure S6b), 19.8 ± 0.4 ps (HT48012, Figure S6c), 51.2 ± 3.7 ps (HT49010, Figure S6d), and 83.9 ± 4.4 ps (HT50010, Figure S6e).…”
Section: Resultsmentioning
confidence: 99%
“…The charge carrier transport performance at the interface of perovskite solar cells has also been studied using time-resolved spectroscopy. , However, besides some research on conventional CdS x Se 1– x and PbS NC-doped glasses, the ultrafast charge carrier dynamics of CsPbX 3 NCs embedded in glasses has rarely been reported. Recently, Klimov et al investigated the temperature-dependent time-resolved fluorescence dynamics of CsPbBr 3 NC-doped glasses and confirmed that the biexciton lifetime of CsPbBr 3 NCs was consistent with the colloidal NCs . However, the effects of glass composition/thermal annealing conditions on the charge carrier dynamics of CsPbX 3 NCs remain largely elusive, and understanding of these effects on the carrier kinetics is full of significance to develop the photoelectric device with high stability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the temperature changes from 300 to 20 K, the fluorescence quantum yield of the CsPbBr 3 perovskite becomes larger. 15 The CsPbBr 3 perovskite is implanted into B 2 O 3 −SiO 2 −ZnO oxide glass to improve its thermal stability. After eight thermal cycles between 293 and 413 K, the photoluminescence (PL) intensity did not change.…”
Section: Introductionmentioning
confidence: 99%
“…The CsPbBr 3 perovskite is embedded in the silicate glass matrix to improve its temperature stability. When the temperature changes from 300 to 20 K, the fluorescence quantum yield of the CsPbBr 3 perovskite becomes larger . The CsPbBr 3 perovskite is implanted into B 2 O 3 –SiO 2 –ZnO oxide glass to improve its thermal stability.…”
Section: Introductionmentioning
confidence: 99%